METHOD OF DEVELOPING PHYSICAL QUALITIES OF VOLLEYBALL STUDENTS BASED ON CROSSFIT - ISKANDAROV I.SH. («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article reveals the features of the use of CrossFit tools in the system of physical ftness of volleyball students, which have a positive eﬀect on the development of speed-strength abilities of those involved in volleyball.